Gas barrier film, laminate film, and packaging material
The gas barrier film with a cured epoxy resin and polycarboxylic acid polymer magnesium salt structure addresses the issue of deteriorating barrier properties under stress, maintaining high performance and transparency.
Patent Information
- Application Number
- JP2021575797
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-05
- Filing Date
- 2021-02-02
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-02-02
AI Technical Summary
Existing gas barrier laminates face issues with deteriorating gas barrier properties after bending tests and moist heat treatments, leading to transparency and durability problems due to mechanical stress and chemical reactions.
A gas barrier film comprising a base material with a layer (A) of a cured epoxy resin having four or more epoxy groups and a layer (B) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer, with specific thicknesses of 120-240 nm, enhancing interfacial adhesion and crosslinking to maintain high gas barrier properties.
The film maintains high gas barrier properties from the initial stage and withstands moist heat treatments and bending tests without significant deterioration, ensuring transparency and durability.
Smart Images

Figure 0007616083000005 
Figure 0007616083000006 
Figure 0007616083000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas barrier film, a laminate film, and a package. [Background technology]
[0002] In order to maintain the quality of food, pharmaceuticals, precision electronic parts, chemical products, electronic materials, industrial products, and other products for a long period of time, there is a demand for packaging materials and films with barrier properties that block or significantly reduce the amount of oxygen and water vapor that permeates. For example, food packaging materials are required to suppress deterioration of the contents due to oxidation and to maintain freshness and aroma. Pharmaceutical packaging materials are also required to prevent the active ingredients of the contents from changing in quality. Precision electronic components are also required to prevent the effects of oxygen that permeates the packaging material in order to suppress corrosion of metal parts and prevent insulation failure. Factors that cause such changes and deterioration include oxygen, moisture, light, and heat, but the biggest factor is oxidative deterioration due to oxygen.
[0003] Conventionally, transparent gas barrier films have attracted attention as barrier materials against oxygen, water vapor, etc., in which inorganic oxides such as silicon oxide and aluminum oxide are formed on a film substrate by vacuum deposition, sputtering, ion plating, chemical vapor deposition, etc. However, such transparent gas barrier films are generally films in which inorganic oxides are deposited on the surface of a substrate made of a biaxially oriented polyester film having excellent transparency and rigidity, and therefore, as they are, the inorganic oxide layer is vulnerable to friction, etc., and when produced as a packaging film, there is a problem that the gas barrier performance becomes unstable due to cracks in the inorganic oxide layer caused by rubbing or stretching during post-processing such as printing or lamination or when filling the film with contents, or due to bending during processing or transportation.
[0004] Therefore, in order to protect the inorganic oxide layer from mechanical deterioration due to rubbing, stretching, and bending, and at the same time to improve the barrier performance, various coating-type barrier materials are laminated on the inorganic oxide layer.
[0005] For example, Patent Document 1 describes a method for producing a gas barrier laminate, which comprises forming a layer (A) containing an alkaline compound of a polyvalent metal on at least one surface of a plastic substrate, applying a solution (b) obtained by dissolving a polycarboxylic acid polymer in a solvent containing at least water to the layer (A) containing an alkaline compound of a polyvalent metal, and then carrying out a heat treatment to remove the solvent, thereby forming a metal ion bridge structure between carboxy groups in the solution (b) with the polyvalent metal ions.
[0006] Patent Document 2 describes a multilayer film having a layer structure in which a polyvalent metal compound-containing layer (B) is adjacent to one or both sides of a polymer layer (A) containing a carboxy group-containing polymer and a polyvalent metal salt of the carboxy group-containing polymer, in which (1) the polymer layer (A) does not contain polyalcohols, and the polymer constituting the polymer layer (A) is only a carboxy group-containing polymer, (2) the polymer layer (A) has a concentration gradient structure in which the concentration of the carboxy group-containing polymer polyvalent metal salt in the polymer layer (A) continuously decreases in the thickness direction from the adjacent surface with the polyvalent metal compound-containing layer (B), and (3) the infrared absorption spectrum of the polymer layer (A) is determined to be at a wave number of 1560 cm. -1 Absorption peak height A at 1560 and wave number 1700cm -1 The height of the absorption peak at A 1700 Peak ratio A 1560 / A 1700 (4) the oxygen permeability of the multilayer film is 500 cm or less under the conditions of a temperature of 30°C and a relative humidity of 0%, and a temperature of 30°C and a relative humidity of 80%. 3 A gas barrier multilayer film having a gas barrier strength of 0.01% or less is described. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2010 / 001836 [Patent Document 2] International Publication No. 2005 / 037535 Summary of the Invention [Problem to be solved by the invention]
[0008] Recently, there has been a demand not only for high gas barrier properties from the initial stage of production, but also for the high gas barrier properties to not deteriorate even after moist heat treatment, and further for the gas barrier properties not to deteriorate even after moist heat treatment, when the film is processed or folded during transportation. However, the gas barrier laminate produced by the production method of Patent Document 1 has a polyurethane layer (white) having basic fine particles dispersed therein and a polycarboxylic acid layer (colorless and transparent) laminated therein, and a neutralization reaction occurs at the interface between these two layers, resulting in a transparent laminate, but some white color remains due to uneven layer thickness, and heat shrinkage due to neutralization heat is likely to occur, resulting in problems with transparency and wrinkles, etc. In addition, the gas barrier laminate produced by the production method of Patent Document 1 has a problem in that the gas barrier property is significantly deteriorated after a bending test (Gelbo flex test). Furthermore, the gas barrier multilayer film of Patent Document 2 has problems in that the gas barrier properties are insufficient even in the initial stage of production, and the gas barrier properties are significantly deteriorated after a bending test (Gelbo flex test).
[0009] The present invention has been made in consideration of the above-mentioned circumstances, and a first object of the present invention is to provide a gas barrier film and laminate film which have high gas barrier properties and transparency from the initial stage of production, and whose gas barrier properties are resistant to deterioration even after moist heat treatment and even after a Gelbo Flex test following moist heat treatment, and a package including the laminate film. [Means for solving the problem]
[0010] The gas barrier film of the present invention comprises a substrate and a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule; a layer (B) adjacent to the layer (A) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer; The layer (B) has a thickness of 120 nm or more and 240 nm or less.
[0011] In the gas barrier film of the present invention, the oxygen permeability at a temperature of 23° C. and a relative humidity of 60% is 1.00 cc / m 2 It is preferable that the gas barrier capacity is 1000 g / kg or less from the viewpoint of having high gas barrier properties from the initial stage of production.
[0012] The first laminate film of the present invention comprises a gas barrier film having a substrate, a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule, and a layer (B) adjacent to the layer (A) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer, the layer (B) having a thickness of 120 nm or more and 240 nm or less; and a sealant layer.
[0013] In the first laminate film of the present invention, the oxygen permeability after the boiling test at a temperature of 23° C. and a relative humidity of 60% is 1.00 cc / m 2 ·day·atm or less, and After the boil test, the Gelbo Flex test was performed under conditions of 23°C and 50% relative humidity according to ASTM F392. The oxygen permeability at 23°C and 60% relative humidity was 1.00cc / m 2 It is preferable that the gas barrier property is less likely to deteriorate after the moist heat treatment and further after the Gelbo Flex test after the moist heat treatment, so that the gas barrier property is less likely to deteriorate after the moist heat treatment.
[0014] In the first laminate film of the present invention, the peel strength after the boiling test is 3.0 N / 15 mm or more in a T-peel test according to JIS K6854-3, and From the viewpoint of durability, it is preferable that the peel strength measured by attaching water to the peeled surface after the boiling test is 3.0 N / 15 mm or more in a T-peel test in accordance with JIS K6854-3.
[0015] The second laminate film of the present invention includes a gas barrier film having a substrate, a layer (A') containing a cured product of an epoxy resin, and a layer (B') adjacent to the layer (A') containing a polycarboxylic acid polymer and a polyvalent metal salt of the polycarboxylic acid polymer, the layer (B') having a thickness of 120 nm or more and 240 nm or less; and a sealant layer, After the boiling test, the oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 1.00cc / m 2 ·day·atm or less, and After the boil test, the Gelbo Flex test was performed under conditions of 23°C and 50% relative humidity according to ASTM F392. The oxygen permeability at 23°C and 60% relative humidity was 1.00cc / m 2 ·day·atm or less, The peel strength after the boiling test is 3.0N / 15mm or more in a T-peel test conforming to JIS K6854-3, and After the boil test, the peel strength measured by applying water to the peeled surface is 3.0N / 15mm or more in a T-peel test in accordance with JIS K6854-3.
[0016] The packaging body of the present invention is characterized by comprising the first laminate film of the present invention or the second laminate film of the present invention. Effect of the Invention
[0017] The present invention can provide a gas barrier film and laminate film that have high gas barrier properties and transparency from the initial stage of production, and whose gas barrier properties are resistant to deterioration even after moist heat treatment and even after a Gelbo Flex test, as well as a package including the laminate film. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the gas barrier film of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of a laminate film including the gas barrier film of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view illustrating a method for a peel test of a laminate film. [Figure 4] FIG. 4 is a schematic cross-sectional view illustrating a method for a peel test of a laminate film. [Diagram 5] FIG. 5 is a diagram showing the change in tensile stress with respect to the distance S between the grippers 31 and 32 during a peel test of a laminate film. [Figure 6] FIG. 6 shows the results of element distribution analysis by EDX (energy dispersive X-ray analysis) in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The gas barrier film and laminate film according to the present invention, and the packaging body including the laminate film will be described in detail below. In the drawings attached to this specification, for the convenience of illustration and ease of understanding, the scale and the aspect ratio may be appropriately changed and exaggerated from those of the actual objects. In this specification, (meth)acrylic means both acrylic and methacrylic. In addition, in this specification, the use of "to" indicating a numerical range is used to mean that the numerical values before and after it are included as the lower limit and upper limit.
[0020] I. Gas barrier film The gas barrier film of the present invention comprises a substrate and a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule; a layer (B) adjacent to the layer (A) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer; The layer (B) has a thickness of 120 nm or more and 240 nm or less.
[0021] FIG. 1 is a schematic cross-sectional view showing an example of the gas barrier film of the present invention. As shown in FIG. 1, the gas barrier film 10 of the present invention has a substrate 11, the layer (A) 12, and the layer (B) 13 adjacent to the layer (A) 12, and the layer thickness of the layer (B) 13 is within the above-mentioned specific range.
[0022] The gas barrier film of the present invention comprises a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule, and a layer (B) adjacent to the layer (A) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer. Since the thickness of the layer (B) is 120 nm or more and 240 nm or less, the gas barrier film has high gas barrier properties from the initial stage of production and is resistant to deterioration of the gas barrier properties even after moist heat treatment as a laminate film and further after a Gelbo flex test. The layer (A) used in the present invention contains a cured product of an epoxy resin having four or more epoxy groups in one molecule, and thus has a high crosslink density and improved gas barrier properties. The layer (B) used in the present invention has a specific layer thickness and contains a magnesium salt of a polycarboxylic acid polymer, and thus has improved gas barrier properties due to the presence of a crosslinked structure of the polycarboxylic acid polymer by magnesium. Furthermore, the epoxy group of the epoxy resin having four or more epoxy groups in one molecule of the layer (A) and the carboxy group of the polycarboxylic acid polymer of the layer (B) undergo a crosslinking reaction at the interface between the layer (A) and the layer (B), thereby improving the interfacial adhesion between the layer (A) and the layer (B), and increasing the crosslink density at the interface to improve the gas barrier properties, and it is presumed that the gas barrier properties are unlikely to deteriorate even after moist heat treatment and even after a Gelbo flex test. If the thickness of layer (B) is smaller than the specific range, it is presumed that the gas barrier property of the layer will be insufficient, whereas if the thickness of layer (B) is larger than the specific range, the layer will be more susceptible to moisture absorption and the layer density will be insufficient, resulting in deterioration of the gas barrier property, or the gas barrier property will be deteriorated after a Gelbo Flex test, and further the interfacial adhesion between layers (A) and (B) will be insufficient, causing layer (B) to be easily peeled off after moist heat treatment. In the present invention, by having the layer (A) and the layer (B) having a specific layer thickness adjacent to each other, it is presumed that a synergistic effect between these layers and the interfaces between the layers realizes high gas barrier properties from the initial stage of production, and also realizes gas barrier properties that are resistant to deterioration even after moist heat treatment and further after a Gelbo flex test. In addition, according to the layer structure of the gas barrier film of the present invention, since the magnesium salt of the polycarboxylic acid polymer can be formed in advance, unevenness and thermal shrinkage are unlikely to occur during the lamination process, and since it is a thin film, there is an advantage that the transparency of the gas barrier film, laminate film, and packaging material including the laminate film is not impaired and the appearance is likely to be good. The substrate, layers and the like contained in the gas barrier film of the present invention will be described below in order.
[0023] <Base material> The substrate used in the gas barrier film of the present invention can be any resin substrate such as a film or sheet made of a resin that satisfies the mechanical, physical and chemical strength, heat resistance and texture required of the packaging material for the contents to be filled and packaged.
[0024] Specifically, films or sheets of various resins such as polyethylene resins, polypropylene resins, polyolefin resins such as cyclic polyolefin resins, fluorine resins, polystyrene resins, acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), polyvinyl chloride resins, poly(meth)acrylic resins, polycarbonate resins, polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, and polyethylene furanolate, polyamide resins such as various nylons, polyimide resins, polyamideimide resins, polyarylphthalate resins, silicone resins, polysulfone resins, polyphenylene sulfide resins, polyethersulfone resins, polyurethane resins, acetal resins, cellulose resins, and mixtures thereof can be used. As the films or sheets of various resins, for example, films or sheets of various resins stretched in uniaxial or biaxial directions using a tenter system or a tubular system can be used. The substrate may be of single layer construction or of two or more laminated layers, for example, formed by co-melt extrusion or other lamination.
[0025] As the substrate, from the viewpoints of gas barrier properties, durability, and versatility, films or sheets made of various polyamide resins such as nylon, polyester resins, or polyolefin resins are preferably used.
[0026] Furthermore, the various resin films or sheets used for the substrate may contain one or more additives, such as pigments, antioxidants, antistatic agents, UV absorbers, lubricants, plasticizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, thread friction reducers, release agents, ion exchange agents, inorganic compounds such as inorganic oxides, and inorganic layered compounds, as necessary.
[0027] The thickness of the various resin films or sheets used as the substrate may be appropriately selected depending on the packaging material of the contents to be filled and packaged, and is not particularly limited, but is usually 3 to 200 μm, and preferably 9 to 100 μm.
[0028] <Layer(A)> The layer (A) contains a cured product of an epoxy resin having four or more epoxy groups in one molecule, i.e., the layer (A) contains a reaction product of an epoxy resin having four or more epoxy groups in one molecule and an epoxy resin curing agent. Epoxy resins having four or more epoxy groups in one molecule include saturated or unsaturated aliphatic compounds, alicyclic compounds, aromatic compounds, heterocyclic compounds, or combinations thereof. The epoxy groups may be contained as, for example, glycidyl groups, alicyclic epoxy groups such as 3,4-epoxycyclohexyl, or epoxy groups directly bonded to an alicyclic skeleton.
[0029] Examples of epoxy resins having four or more epoxy groups in one molecule include epoxy resins having a glycidyl amine moiety or a glycidyl ether moiety derived from a compound having two or more amino groups or four or more hydroxyl groups, which is a saturated or unsaturated aliphatic compound, alicyclic compound, aromatic compound, heterocyclic compound, or a combination thereof; and compounds having an alicyclic epoxy group moiety derived from a compound having four or more carboxy groups, which is a saturated or unsaturated aliphatic compound, alicyclic compound, aromatic compound, heterocyclic compound, or a combination thereof. Specifically, for example, epoxy resins having a glycidylamine moiety derived from a xylylenediamine such as metaxylylenediamine, epoxy resins having a glycidylamine moiety derived from 1,3-bis(aminomethyl)cyclohexane, epoxy resins having a glycidylamine moiety derived from diaminodiphenylmethane, epoxy resins having a glycidyl ether moiety derived from phenol novolac, epoxy resins having a glycidyl ether moiety derived from cresol novolac, epoxy resins having a glycidyl ether moiety derived from an aliphatic polyhydric alcohol such as sorbitol polyglycidyl ether and pentaerythritol polyglycidyl ether, epoxy resins having a glycidyl ether moiety derived from a polyether alcohol obtained by adding an alkylene oxide to a phenol having four or more hydroxyl groups in one molecule; compounds having a 3,4-epoxycyclohexylmethyl moiety derived from an aliphatic polycarboxylic acid such as butanetetracarboxylic acid tetra(3,4-epoxycyclohexylmethyl)-modified ε-caprolactone and ethanetetracarboxylic acid tetra(3,4-epoxycyclohexylmethyl); 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (e.g., EHPE3150: manufactured by Daicel, average number of epoxy groups in one molecule is 15); and polymers containing an epoxy group in the repeating unit.
[0030] As the epoxy resin used in the layer (A) of the present invention, an epoxy resin containing an aromatic ring or an aliphatic ring in the molecule is preferable, and an epoxy resin containing an aromatic ring in the molecule is more preferable from the viewpoint of improving the gas barrier property. Specific examples include N,N,N',N'-tetraglycidylmeta-xylylenediamine, N,N,N',N'-tetraglycidyl-4,4'-aminodiphenylmethane, N,N,N',N'-tetraglycidyl-4,4-(4-aminophenyl)-p-diisopropylbenzene, 1,1,2,2-(tetraglycidyloxyphenyl)ethane, 1,1,2,2-tetrabis(hydroxyphenyl)ethane tetraglycidyl ether, and tetraglycidyl-1,3-bisaminomethylcyclohexane. Among them, an epoxy resin containing a skeleton structure represented by the following chemical formula (1) in the molecule is more preferable.
[0031] [ka] From the viewpoint of improving the gas barrier properties, the epoxy resin used in layer (A) of the present invention preferably contains, as a main component, one or more selected from the group consisting of epoxy resins having a glycidylamine moiety derived from meta-xylylenediamine and epoxy resins having a glycidylamine moiety derived from 1,3-bis(aminomethyl)cyclohexane, more preferably contains, as a main component, an epoxy resin having a glycidylamine moiety derived from meta-xylylenediamine, and even more preferably contains, as a main component, N,N,N',N'-tetraglycidyl meta-xylylenediamine represented by the following chemical formula (1a). Here, being contained as a main component means that the epoxy resin is contained in an amount of 50 mass% or more, preferably 70 mass% or more, more preferably 90 mass% or more, and may be 100 mass% based on the total amount of the epoxy resin contained in layer (A).
[0032] [ka]
[0033] The epoxy resin contained in the layer (A) may be used alone or in combination of two or more kinds. The epoxy resin contained in layer (A) preferably contains an epoxy resin having four or more epoxy groups in one molecule as a main component, preferably at 70% by mass or more, more preferably at 90% by mass or more, and may be 100% by mass. The epoxy resin contained in the layer (A) may contain an epoxy resin having three or less epoxy groups in one molecule, so long as the effect of the present invention is not impaired. The epoxy resin having three or less epoxy groups in one molecule may be an epoxy resin having two or more epoxy groups in one molecule. As the epoxy resin having two or three epoxy groups in one molecule, a conventionally known epoxy resin can be appropriately selected and used. For example, an epoxy resin having a glycidylamine moiety and / or a glycidyl ether moiety derived from paraaminophenol, an epoxy resin having a glycidyl ether moiety derived from bisphenol A, an epoxy resin having a glycidyl ether moiety derived from bisphenol F, an epoxy resin having a glycidyl ether moiety derived from resorcinol, etc. can be mentioned.
[0034] The epoxy resin used in the present invention can be produced by a conventionally known production method, and is obtained by reacting various alcohols, phenols, and amines with epihalohydrin. For example, an epoxy resin having a glycidylamine moiety derived from metaxylylenediamine can be obtained by adding epichlorohydrin to metaxylylenediamine. The epoxy resin used in the present invention may be appropriately selected from commercially available products.
[0035] Meanwhile, the epoxy resin curing agent used for curing the epoxy resin may be any of an aliphatic compound, an alicyclic compound, an aromatic compound, a heterocyclic compound, or a combination thereof, and commonly used epoxy resin curing agents such as polyamines, phenols, acid anhydrides, or carboxylic acids may be used.
[0036] Specific examples of polyamines include aliphatic amines such as ethylenediamine, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine; aliphatic amines having an aromatic ring such as metaxylylenediamine and paraxylylenediamine; alicyclic amines such as 1,3-bis(aminomethyl)cyclohexane, isophoronediamine, and norbornenediamine; and aromatic amines such as diaminodiphenylmethane and metaphenylenediamine. Also usable are modification products of these polyamines as raw materials with epoxy resins or monoglycidyl compounds, addition reaction products with epichlorohydrin, reaction products with polyfunctional compounds having at least one acyl group which can form an amide group moiety and form an oligomer upon reaction with these polyamines, and reaction products between polyfunctional compounds having at least one acyl group which can form an amide group moiety and form an oligomer upon reaction with these polyamines and at least one type of monovalent carboxylic acid and carboxylic acid derivative.
[0037] Phenols include poly-substituent monomers such as catechol, resorcinol, and hydroquinone, and resol-type phenolic resins. In addition, examples of acid anhydrides or carboxylic acids that can be used include aliphatic acid anhydrides such as dodecenylsuccinic anhydride and polyadipic anhydride, alicyclic acid anhydrides such as (methyl)tetrahydrophthalic anhydride and (methyl)hexahydrophthalic anhydride, aromatic acid anhydrides such as phthalic anhydride, trimellitic anhydride and pyromellitic anhydride, and these carboxylic acids.
[0038] From the viewpoint of improving the gas barrier property, an epoxy resin curing agent containing an aromatic ring in the molecule is preferred, and an epoxy resin curing agent containing the skeletal structure represented by the above chemical formula (1) in the molecule is more preferred. Specifically, it is more preferable to use meta-xylylenediamine or para-xylylenediamine, and modified reaction products of these as raw materials with epoxy resins or monoglycidyl compounds, addition reaction products with epichlorohydrin, reaction products with polyfunctional compounds having at least one acyl group which can form an amide group moiety and form an oligomer upon reaction with these polyamines, and reaction products of polyfunctional compounds having at least one acyl group which can form an amide group moiety and form an oligomer upon reaction with these polyamines with at least one monovalent carboxylic acid and carboxylic acid derivative.
[0039] From the viewpoints of high gas barrier properties and adhesion to various materials, it is particularly preferable to use, as the epoxy resin curing agent, a reaction product of the following (I) and (II), or a reaction product of (I), (II) and (III). (I) Metaxylylenediamine or paraxylylenediamine (II) A polyfunctional compound having at least one acyl group capable of forming an amide group moiety and forming an oligomer by reacting with a polyamine. (III) At least one monovalent carboxylic acid or carboxylic acid derivative having 1 to 8 carbon atoms
[0040] Examples of the (II) polyfunctional compound having at least one acyl group that can form an amide group moiety and form an oligomer upon reaction with a polyamine include carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, succinic acid, malic acid, tartaric acid, adipic acid, isophthalic acid, terephthalic acid, pyromellitic acid, and trimellitic acid, and derivatives thereof, such as esters, amides, acid anhydrides, and acid chlorides, with acrylic acid, methacrylic acid, and derivatives thereof being particularly preferred. Examples of the monovalent carboxylic acid having 1 to 8 carbon atoms in (III) include formic acid, acetic acid, propionic acid, butyric acid, lactic acid, glycolic acid, and benzoic acid, and also include derivatives thereof, such as esters, amides, acid anhydrides, and acid chlorides. These may be used in combination with the polyfunctional compound to react with a polyamine (metaxylylenediamine or paraxylylenediamine).
[0041] In the present invention, the reaction ratio in the reaction for synthesizing the epoxy resin curing agent is preferably adjusted so that the content of amide groups is adjusted from the viewpoints of gas barrier property and adhesiveness, and the molar ratio of the polyfunctional compound to the polyamine component is preferably within the range of 0.3 to 0.95.
[0042] The blending ratio of the epoxy resin and the epoxy resin curing agent forming the layer (A) of the present invention may be appropriately adjusted, and will be described in detail in the manufacturing method described later. In the present invention, since the epoxy group contained in the layer (A) of the present invention undergoes a crosslinking reaction with the carboxy group contained in the layer (B) at the interface adjacent to the layer (B), it is preferable to blend the epoxy resin curing agent so that the epoxy group remains at least at the interface of the layer (A). Layer (A) of the present invention preferably contains a reaction product of an epoxy resin and an epoxy resin curing agent derived from an epoxy resin and an epoxy resin curing agent in an amount of 80 mass % or more, and more preferably 90 mass % or more, based on the entire layer (A).
[0043] The layer (A) of the present invention may further contain other components as long as the effects of the present invention are not impaired. Examples of other components include surfactants, inorganic fillers, antioxidants, other resins such as tackifying resins, silane coupling agents, oxygen absorbers, deodorants, flame retardants, UV absorbers, weather resistance agents, light resistance agents, antibacterial and disinfectant agents, etc.
[0044] Layer (A) of the present invention does not basically need to contain magnesium ions or magnesium compounds contained in layer (B), and does not need to contain magnesium ions or magnesium compounds except near the interface with layer (B). On the other hand, layer (A) of the present invention may contain anions derived from the magnesium compound used to form the magnesium salt contained in layer (B). The anions derived from the magnesium compound may be removed during production, but may remain. Examples of anions derived from magnesium compounds include chloride ions, nitrate ions, sulfate ions, carbonate ions, acetate ions, and phosphate ions. In addition, the composition may further contain an ion scavenger for capturing anions derived from these magnesium compounds.
[0045] The layer thickness of the layer (A) has a lower limit of preferably 250 nm or more, more preferably 300 nm or more, from the viewpoint of having high gas barrier properties from the initial stage of production, and suppressing deterioration of the gas barrier properties after moist heat treatment and even after the Gelbo Flex test, and suppressing layer peeling after moist heat treatment. On the other hand, the upper limit is preferably 3000 nm or less, more preferably 2500 nm or less, and may be 900 nm or less.
[0046] <Layer (B)> The layer (B) is located adjacent to the layer (A) and contains a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer. The polycarboxylic acid polymer used in the present invention is a polymer having two or more carboxy groups in the molecule. Since layer (B) is located adjacent to layer (A), a carboxy group of the polycarboxylic acid polymer in layer (B) and an epoxy group of the tetrafunctional or higher epoxy resin in layer (A) undergo a three-dimensional crosslinking reaction at the interface between layer (B) and layer (A), improving interlayer adhesion and gas barrier properties. Furthermore, since the layer (B) contains a polycarboxylic acid polymer crosslinked with magnesium ions, it improves the gas barrier property.
[0047] Representative examples of polycarboxylic acid polymers include homopolymers of carboxyl group-containing unsaturated monomers, copolymers of carboxyl group-containing unsaturated monomers, copolymers of carboxyl group-containing unsaturated monomers with other polymerizable monomers, and polysaccharides containing carboxyl groups in the molecule (also called "acidic polysaccharides"). The carboxy group includes not only a free carboxy group but also an acid anhydride group (specifically, a dicarboxylic acid anhydride group). The acid anhydride group may be partially ring-opened to form a carboxy group. A part of the carboxy group may be neutralized with an alkali. In this case, the degree of neutralization is preferably 20% or less.
[0048] In addition, a graft polymer obtained by graft polymerizing a carboxyl-containing unsaturated monomer onto a polymer not containing a carboxyl group, such as polyolefin, can also be used as the polycarboxylic acid polymer. A polymer having a hydrolyzable ester group, such as an alkoxycarbonyl group (e.g., a methoxycarbonyl group), can also be hydrolyzed to convert the ester group into a carboxyl group, and the resulting polymer can be used as the polycarboxylic acid polymer.
[0049] The carboxyl group-containing unsaturated monomer is preferably an α,β-monoethylenically unsaturated carboxylic acid. Thus, the polycarboxylic acid polymer includes a homopolymer of an α,β-monoethylenically unsaturated carboxylic acid, a copolymer of two or more kinds of α,β-monoethylenically unsaturated carboxylic acids, and a copolymer of an α,β-monoethylenically unsaturated carboxylic acid and another polymerizable monomer. The other polymerizable monomer is typically an ethylenically unsaturated monomer.
[0050] Examples of α,β-monoethylenically unsaturated carboxylic acids include unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid; unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid; unsaturated dicarboxylic anhydrides such as maleic anhydride and itaconic anhydride; and mixtures of two or more of these. Among these, at least one α,β-monoethylenically unsaturated carboxylic acid selected from the group consisting of acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid is preferred, and at least one α,β-monoethylenically unsaturated carboxylic acid selected from the group consisting of acrylic acid, methacrylic acid, and maleic acid is more preferred.
[0051] Examples of other polymerizable monomers copolymerizable with α,β-monoethylenically unsaturated carboxylic acids, particularly ethylenically unsaturated monomers, include ethylene; α-olefins such as propylene, 1-butene, 1-pentene, 1-hexene, and 1-octene; saturated carboxylic acid vinyl esters such as vinyl acetate; acrylic acid alkyl esters such as methyl acrylate and ethyl acrylate; methacrylic acid alkyl esters such as methyl methacrylate and ethyl methacrylate; chlorine-containing vinyl monomers such as vinyl chloride and vinylidene chloride; fluorine-containing vinyl monomers such as vinyl fluoride and vinylidene fluoride; unsaturated nitriles such as acrylonitrile and methacrylonitrile; aromatic vinyl monomers such as styrene and α-methylstyrene; itaconic acid alkyl esters; etc. These ethylenically unsaturated monomers can be used alone or in combination of two or more. In addition, when the polycarboxylic acid polymer is a copolymer of an α,β-monoethylenically unsaturated carboxylic acid and a saturated carboxylic acid vinyl ester such as vinyl acetate, a copolymer obtained by saponifying the copolymer to convert the saturated carboxylic acid vinyl ester units into vinyl alcohol units can also be used.
[0052] Examples of the carboxyl group-containing polysaccharides include acidic polysaccharides having a carboxyl group in the molecule, such as alginic acid, carboxymethylcellulose, and pectin. These acidic polysaccharides can be used alone or in combination of two or more. The acidic polysaccharides can also be used in combination with a (co)polymer of an α,β-monoethylenically unsaturated carboxylic acid.
[0053] When the polycarboxylic acid polymer used in the present invention is a copolymer of an α,β-monoethylenically unsaturated carboxylic acid and another ethylenically unsaturated monomer, from the viewpoints of the gas barrier properties, hot water resistance, and water vapor resistance of the resulting film, the copolymer composition preferably has an α,β-monoethylenically unsaturated carboxylic acid monomer composition of 60 mol % or more, more preferably 80 mol % or more, and particularly preferably 90 mol % or more.
[0054] The polycarboxylic acid polymer is preferably a homopolymer or copolymer obtained by polymerization of only α,β-monoethylenically unsaturated carboxylic acid, since it is easy to obtain a film having excellent gas barrier properties, moisture resistance, water resistance, hot water resistance, and water vapor resistance, and also excellent gas barrier properties under high humidity conditions. When the polycarboxylic acid polymer is a (co)polymer consisting of only α,β-monoethylenically unsaturated carboxylic acid, its preferred specific examples are homopolymers, copolymers, and mixtures of two or more thereof obtained by polymerization of at least one α,β-monoethylenically unsaturated carboxylic acid selected from the group consisting of acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid. Among these, homopolymers and copolymers of at least one α,β-monoethylenically unsaturated carboxylic acid selected from the group consisting of acrylic acid, methacrylic acid, and maleic acid are more preferred.
[0055] As the polycarboxylic acid polymer, polyacrylic acid, polymethacrylic acid, maleic acid polymer, and a mixture of two or more of them are particularly preferred. As the acidic polysaccharide, alginic acid polymer is preferred. Among these, polyacrylic acid is particularly preferred because it is relatively easy to obtain and a film having excellent physical properties can be easily obtained.
[0056] The molecular weight of the polycarboxylic acid polymer is not particularly limited, but from the viewpoint of film formability and film physical properties, the number average molecular weight may be in the range of 2,000 to 10,000,000, 5,000 to 1,000,000, or 10,000 to 500,000. In particular, from the viewpoint of improving the gas barrier property after wet heat treatment, the weight average molecular weight of the polycarboxylic acid polymer is preferably in the range of 20,000 to 5,000,000, and more preferably in the range of 200,000 to 1,000,000. The number average molecular weight and the weight average molecular weight can be measured by gel permeation chromatography (GPC). In GPC measurement, the number average molecular weight and the weight average molecular weight of a polymer are generally measured in terms of standard polystyrene.
[0057] As the polymer constituting the layer (B), in addition to the polycarboxylic acid polymer, other polymers may be mixed and used within the range that does not impair the properties of the film such as gas barrier property, hot water resistance, water vapor resistance, etc. Among them, it is preferable that the polymer constituting the layer (B) contains only a polycarboxylic acid polymer.
[0058] The polycarboxylic acid polymer used as the raw material is preferably one having an oxygen permeability of 150 cc / m at a temperature of 23°C and a relative humidity of 60% for a dry coating film formed by using the polymer alone. 2 ·day·atm or less, preferably 50cc / m 2 ·day·atm or less, particularly preferably 10cc / m 2 From the viewpoint of gas barrier properties, it is preferable that the gas permeability is less than 1000 m / day atm.
[0059] The oxygen permeability of the dry coating film formed by using only the polycarboxylic acid polymer used as the raw material can be determined by the following method. The polycarboxylic acid polymer is dissolved in water to prepare an aqueous solution with a concentration of 10% by mass. This aqueous solution is applied to a plastic film substrate (e.g., a nylon film having a thickness of 15 μm) having a relatively high oxygen permeability using a bar coater, and dried to prepare a coating film having a dry coating film of the polycarboxylic acid polymer with a dry thickness of 1 μm. The oxygen permeability of the obtained coating film is measured at a temperature of 23° C. and a relative humidity of 60%, similarly to the gas barrier film described later. If the oxygen permeability of the obtained coating film having the dry coating film of the polycarboxylic acid polymer is 1 / 10 or less of the oxygen permeability of the plastic film used as the substrate, the measured oxygen permeability can be regarded as the oxygen permeability of the dry coating film formed by using the polycarboxylic acid polymer alone.
[0060] Moreover, the layer (B) contains the magnesium salt of the polycarboxylic acid polymer. Mg in layer (B) 2+ From the viewpoint of gas barrier properties, the total of Mg in layer (B) is preferably 0.2 chemical equivalents or more, more preferably 0.4 chemical equivalents or more, and even more preferably 0.5 chemical equivalents or more, based on the total carboxyl groups of the polycarboxylic acid polymer in layer (B). 2+ is preferably 1.0 chemical equivalent or less, more preferably 0.9 chemical equivalent or less, and even more preferably 0.8 chemical equivalent or less, based on the total carboxy groups of the polycarboxylic acid polymer in layer (B) from the viewpoint of gas barrier properties and suppressing deterioration of adhesion. The total carboxy groups of the polycarboxylic acid polymer refers to the carboxy groups (-COOH) of the polycarboxylic acid polymer that have not formed a salt and the carboxy ions (-COOH) contained in the polycarboxylic acid polymer that have formed a salt. - ) in the layer (B). 2+ The sum of Mg that forms a salt with the polycarboxylic acid polymer is 2+and Mg contained in magnesium compounds 2+ The above refers to the sum of the above.
[0061] The layer (B) may contain a magnesium compound which does not form a salt with the polycarboxylic acid polymer. The magnesium compound is preferably a compound that is easily soluble in water, from the viewpoint that the magnesium salt of the polycarboxylic acid polymer in layer (B) is dispersed in layer (B) and the barrier property is improved. Magnesium chloride, magnesium nitrate, magnesium sulfate, magnesium acetate, etc. are preferably used. Magnesium chloride, magnesium nitrate, and magnesium sulfate can also be prepared by dissolving a magnesium compound that is poorly soluble in water, such as magnesium hydroxide, magnesium carbonate, magnesium oxide, or magnesium phosphate, under acidic conditions, such as in the presence of hydrochloric acid, nitric acid, or sulfuric acid.
[0062] In the present invention, layer (B) may contain anions such as chloride ions and nitrate ions derived from the magnesium compound, but the anions derived from the magnesium compound when forming a magnesium salt in layer (B) tend to remain in layer (A) rather than in layer (B). It is preferable that the anions derived from the magnesium compound are contained in a larger amount in layer (A) than in layer (B), and further, it is preferable that they are not present on the outermost surface of layer (B) (the surface of layer (B) opposite to the surface having layer (A)). The anions derived from these magnesium compounds can be analyzed, for example, by element distribution analysis using EDX (energy dispersive X-ray analysis), depth profile analysis using XPS (X-ray photoelectron spectroscopy), or time-of-flight secondary ion mass spectrometry (TOF-SIMS).
[0063] Layer (B) of the present invention preferably contains 80% by mass or more, and more preferably 90% by mass or more, of the polycarboxylic acid polymer, magnesium ions, and anions derived from a magnesium compound based on the entire layer (B).
[0064] Layer (B) may contain other components within the scope of the present invention, such as surfactants, inorganic fillers, antioxidants, other resins such as tackifier resins, silane coupling agents, ion scavengers, oxygen absorbers, deodorants, flame retardants, UV absorbers, weather resistance agents, light resistance agents, antibacterial and disinfectant agents.
[0065] The layer thickness of layer (B) is 120 nm or more and 240 nm or less in order to have high gas barrier properties from the initial stage of production and to suppress deterioration of the gas barrier properties after moist heat treatment and even after a Gelbo Flex test, and to suppress layer peeling after moist heat treatment. In particular, from the viewpoint of initial barrier properties, the layer thickness of layer (B) is preferably 140 nm or more and 200 nm or less.
[0066] <Other layers> The gas barrier film of the present invention may further include other layers. The gas barrier film of the present invention has the specific layer (B) having a specific layer thickness adjacent to the specific layer (A) in combination, and therefore has improved gas barrier properties, and does not need to contain an inorganic oxide layer such as an inorganic oxide vapor deposition film. Therefore, the layer (A) may be located adjacent to the substrate. However, the gas barrier film of the present invention does not preclude an embodiment in which an inorganic oxide layer is further present between the substrate and the layer (A), for example. Examples of the other layers include a layer made of a metal foil obtained by rolling a metal, an adhesive layer, a printed layer, a resin layer obtained by co-extrusion with a substrate, and a metal vapor deposition layer. When the substrate has two or more other layers, the other layers may have the same composition or different compositions. The other layers may be present on one or more of the surface of the substrate opposite to the surface having layers (A) and (B), between the substrate and layer (A), or on the surface of layer (B) opposite to the surface having layer (A).
[0067] As the other layers, layers known in the art can be appropriately selected and used. The inorganic oxide layer may be a vapor-deposited film of an inorganic oxide such as silicon oxide, alumina, etc. The thickness of the vapor-deposited film of the inorganic oxide varies depending on the type of inorganic oxide used, but can be arbitrarily selected within the range of, for example, 20 to 2000 Å, preferably 50 to 500 Å, from the viewpoint of gas barrier performance. As the metal foil, any conventionally known metal foil can be used. From the viewpoints of oxygen barrier property, water vapor barrier property, light blocking property for preventing the transmission of visible light and ultraviolet light, and design property of gloss, aluminum foil and the like are preferable. The print layer can be formed by a conventionally known method using a conventionally known pigment or dye. The adhesive layer is an adhesive layer formed to bond any two layers together by lamination. For example, one-liquid or two-liquid cured or non-cured vinyl, (meth)acrylic, polyamide, polyester, polyether, polyurethane, epoxy, rubber, and other solvent, water-based, or emulsion adhesives can be used as lamination adhesives. The thickness of the adhesive layer can be selected from the range of, for example, 0.1 to 5 μm, preferably 0.5 to 3 μm.
[0068] <Gas barrier film properties> The gas barrier film of the present invention has high gas barrier properties from the initial stage of production, and therefore has an oxygen permeability of 1.00 cc / m at a temperature of 23° C. and a relative humidity of 60%. 2 ·day·atm or less is preferable, and 0.90cc / m 2 ·day·atm or less is more preferable, and 0.80cc / m 2 It is even more preferable that the temperature is 100°C or less. Specifically, the oxygen permeability at a temperature of 23° C. and a relative humidity of 60% can be measured by the method described in the Examples below.
[0069] <Method of manufacturing gas barrier film> The method for producing the gas barrier film of the present invention is not particularly limited as long as it is possible to produce the gas barrier film of the present invention. For example, the following production method is preferably used. The method for producing the gas barrier film of the present invention includes the following steps: Providing a substrate; A step of preparing a curable composition for forming layer (A), which contains an epoxy resin having four or more epoxy groups in one molecule and an epoxy resin curing agent; A step of preparing a layer (B) forming composition containing a polycarboxylic acid polymer and a magnesium compound; a step of coating the layer (A)-forming curable composition on the substrate, and then drying and heating the coating as necessary to form a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule; and applying the composition for forming layer (B) directly onto layer (A), and then drying and heating the coating as necessary to form layer (B) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer and having a layer thickness of 120 nm or more and 240 nm or less adjacent to layer (A).
[0070] (Process of preparing the substrate) In the process of preparing the substrate, as described above, the substrate may be prepared by arbitrarily selecting a resin film or sheet that satisfies the mechanical, physical, and chemical strength, heat resistance, and texture required of the packaging material for the contents to be filled and packaged.
[0071] (Step of Preparing Curable Composition for Forming Layer (A)) The curable composition for forming layer (A) can be prepared by mixing the above-mentioned epoxy resin having four or more epoxy groups in one molecule, the above-mentioned epoxy resin curing agent, and, if necessary, a solvent and other components. The solvent may be appropriately selected from those in which the epoxy resin and the epoxy resin curing agent are soluble. Organic solvents are preferred, and examples thereof include glycol ethers such as 2-methoxyethanol, 2-ethoxyethanol, 2-propoxyethanol, 2-butoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, and 1-propoxy-2-propanol; alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and 2-butanol; aprotic polar solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, and N-methylpyrrolidone; and non-water-soluble solvents such as toluene, xylene, and ethyl acetate. Solvents with relatively low boiling points such as methanol and ethyl acetate are more preferred.
[0072] The blending ratio of the epoxy resin and the epoxy resin curing agent in the curable composition for forming layer (A) may be appropriately adjusted. From the viewpoints of improving the gas barrier property and improving the adhesion, specifically, the ratio of the number of active hydrogens in the epoxy resin curing agent to the number of epoxy groups in the epoxy resin is preferably 0.1 to 5.0, more preferably 0.2 to 3.0, and even more preferably 0.3 to 1.5, and may be less than 1.
[0073] (Step of Preparing Layer (B)-Forming Composition) The layer (B) forming composition can be prepared by mixing the polycarboxylic acid polymer, the magnesium compound, a solvent, and, if necessary, other components. The solvent is preferably a solvent that dissolves the polycarboxylic acid polymer and the magnesium compound, and examples of the solvent include water, alcohols such as methyl alcohol and isopropyl alcohol, and polar organic solvents such as dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide, and these solvents may be used alone or in combination of two or more. Of these, the solvent preferably contains water. As the magnesium compound, it is preferable to use it by dissolving it in a solvent in order to allow the crosslinking reaction of the polycarboxylic acid polymer with magnesium ions to proceed throughout the entire layer, and as described above, it is preferable to use a water-soluble magnesium compound such as magnesium chloride, magnesium nitrate, magnesium sulfate, etc. Alternatively, when using a magnesium compound such as magnesium hydroxide that is poorly soluble in water, it is preferable to dissolve it in an acidic aqueous solution in the presence of hydrochloric acid, nitric acid, sulfuric acid, etc. That is, as the curable composition for forming the layer (B), it is preferable to prepare an aqueous solution of the polycarboxylic acid polymer and the magnesium compound. As described above, according to the method for producing a gas barrier film of the present invention, it is possible to form a magnesium salt of a polycarboxylic acid polymer before forming a layer. Therefore, unlike the case where salt formation is carried out by a neutralization reaction or the like after layer formation, unevenness or thermal shrinkage in the layer is less likely to occur, and the appearance is likely to be good.
[0074] The blending ratio of the polycarboxylic acid polymer and the magnesium compound in the layer (B) forming composition is set to be 2+ It is preferable to mix them so that the total of the above is in the above-mentioned chemical equivalent range relative to the total of the carboxy groups of the polycarboxylic acid polymer. The layer (B)-forming composition is preferably blended with a solvent so that the solid content is 1.5 to 9.5 mass %, more preferably 2.0 to 9.0 mass %. In the present invention, the solid content refers to all components other than the solvent, including liquid resins and other components.
[0075] (Step of forming layer (A)) The layer (A)-forming curable composition is applied onto the substrate. If the substrate is a substrate, it is not necessary to apply the composition directly onto the substrate. If another layer is present on the substrate, the layer (A)-forming curable composition is applied directly onto the other layer to form a coating film. The coating film is provided by adjusting the amount of application so that the thickness of the layer (A)-forming curable composition after curing falls within the range of the layer thickness. The coating method can be appropriately selected from known coating methods, and various coating methods such as roll coating, bar coating, gravure coating, and slit coating can be used.
[0076] The coating film is dried and heated as necessary to form a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule. The drying temperature may be appropriately selected depending on the solvent used, and may be, for example, 50 to 170° C., and the drying time may be, for example, 1 to 30 minutes. The heating temperature may be appropriately selected depending on the epoxy resin and epoxy curing agent used, and may be, for example, 50 to 170° C., and the heating time may be, for example, 0.5 to 120 hours. Incidentally, drying and heating may be carried out simultaneously, and known drying and heating means can be appropriately selected and used.
[0077] (Step of forming layer (B)) The layer (B)-forming composition is applied directly onto the layer (A) to form a coating film. The coating film is provided by adjusting the solid content in the layer (B)-forming composition and the coating amount so that the thickness of the layer (B)-forming composition after drying and reaction falls within the range of the layer thickness of the layer (B) of 120 nm to 240 nm. As the coating method, a known coating method can be appropriately selected and used, and the same methods as those described above can be used.
[0078] The coating film is dried and heated as necessary. By drying the solvent, the carboxyl group of the polycarboxylic acid polymer and the magnesium ion undergo a crosslinking reaction to form a magnesium salt of the polycarboxylic acid polymer. Furthermore, by heating during drying, the epoxy group present at the interface of the layer (A) undergoes a crosslinking reaction with the carboxyl group of the polycarboxylic acid polymer. In this way, a layer (B) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer is formed adjacent to the layer (A). Drying or heating may be performed simultaneously. The drying or heating temperature may be appropriately selected depending on the solvent used, and may be, for example, 50 to 170° C., and the drying or heating time may be, for example, 1 to 30 minutes.
[0079] II. Laminate film [First Laminate Film] The first laminate film of the present invention comprises a gas barrier film having a substrate, a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule, and a layer (B) adjacent to the layer (A) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer, the layer (B) having a thickness of 120 nm or more and 240 nm or less; and a sealant layer.
[0080] FIG. 2 is a schematic cross-sectional view showing an example of the laminate film of the present invention. As shown in FIG. 2, the laminate film 20 of the present invention has a substrate 11, the layer (A) 12, the layer (B) 13 adjacent to the layer (A) 12, and a sealant layer 14, in this order. The laminate film 20 of the present invention may further have an adhesive layer (not shown) between the layer (B) 13 and the sealant layer 14 .
[0081] The first laminate film of the present invention comprises the gas barrier film of the present invention described above, and further comprises a sealant layer, and thereby has high gas barrier properties from the initial stage of production due to the same action as the gas barrier film of the present invention described above, and is a laminate film whose gas barrier properties are resistant to deterioration even after moist heat treatment, and even after a Gelbo flex test following moist heat treatment. The laminate film of the present invention further comprises at least a heat-sealable sealant layer in addition to the gas barrier film of the present invention described above, and the heat-sealability is imparted to the film by using the sealant layer as the innermost layer. In the first laminate film of the present invention, the substrate, layer (A), and layer (B) may be the same as those in the gas barrier film of the present invention, and therefore a description thereof will be omitted here.
[0082] <Sealant layer> The heat-sealable resin constituting the sealant layer may be any resin that can melt and fuse with each other by heat, and examples of such resin films or sheets that can be used include polyolefin resins such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear (linear) low-density polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-propylene copolymer, and methylpentene polymer, as well as acid-modified polyolefin resins obtained by modifying these resins with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic anhydride, and fumaric acid. Among these, from the viewpoint of water vapor barrier properties, it is preferable to use a resin film or sheet containing polypropylene as the sealant layer. The above resin films or sheets can be used in a single layer or multilayer configuration and have a thickness of, for example, 5 to 300 μm, preferably 10 to 150 μm.
[0083] <Other layers> The laminate film of the present invention may further include other layers. The laminate film of the present invention may contain other layers similar to those of the gas barrier film of the present invention, and may further contain a resin layer, a light-shielding layer for imparting light-shielding properties, an absorptive / adsorptive layer for absorbing or adsorbing odors, a light-resistant layer, a printed layer, an oxygen-absorbing layer, a flame-retardant layer, a weather-resistant layer, a hard coat layer, an antibacterial / bactericidal layer, a liquid crystal layer, etc. In the laminate film of the present invention, when the laminate film has two or more other layers, each of the other layers may have the same composition or different compositions. The other layers may be present on one or more of the surface of the substrate opposite to the surface having the layers (A) and (B), between the substrate and the layer (A), or between the layer (B) and the sealant layer. As these other layers, layers known in the art can be appropriately selected and used.
[0084] The resin layer is, for example, located between layer (B) and the sealant layer, and a resin film or sheet having excellent mechanical, physical, chemical, etc. strength, excellent puncture resistance, etc., and other excellent heat resistance, moisture resistance, pinhole resistance, transparency, etc., can be used. Specifically, for example, polyester resin, polyamide resin, polyaramid resin, polypropylene resin, polycarbonate resin, polyacetal resin, fluorine resin, and other tough resin films or sheets can be used. The above resin film or sheet may be any of an unstretched film, a uniaxially or biaxially stretched film, etc. In the present invention, the thickness of the resin film or sheet is preferably 10 to 100 μm, particularly preferably 12 to 50 μm.
[0085] <Characteristics of Laminate Film> The laminate film of the present invention has high gas barrier properties from the initial stage of production, and has an oxygen permeability of 1.00 cc / m at a temperature of 23° C. and a relative humidity of 60%. 2 ·day·atm or less is preferable, and 0.90cc / m 2 ·day · atm or less, 0.80cc / m 2 ·day·atm or less is more preferable, and 0.70cc / m 2 ·day·atm or less is more preferable, and 0.50cc / m 2 It is even more preferable that the temperature is 100°C or less. Specifically, the oxygen permeability at a temperature of 23° C. and a relative humidity of 60% can be measured by the method described in the Examples below.
[0086] In addition, the laminate film of the present invention is resistant to deterioration in gas barrier properties even after moist heat treatment and Gelbo flex testing, and has an oxygen permeability of 1.00 cc / m2 at a temperature of 23°C and a relative humidity of 60% after a boil test. 2 ·day·atm or less, and After the boil test, the Gelbo Flex test was performed under conditions of 23°C and 50% relative humidity according to ASTM F392. The oxygen permeability at 23°C and 60% relative humidity was 1.00cc / m 2 It is preferable that the temperature be less than 100°C / day atm. The laminate film of the present invention has an oxygen permeability of 0.95 cc / m at a temperature of 23°C and a relative humidity of 60% after a boil test. 2 ·day·atm or less, and after the boil test and the Gelbo Flex test, the oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 0.95cc / m 2 ·day·atm or less, and after the boiling test, the oxygen transmission rate is 0.90cc / m at a temperature of 23°C and a relative humidity of 60%. 2 ·day·atm or less, and after the boil test and the Gelbo Flex test, the oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 0.90cc / m 2 ·day·atm or less, and after the boiling test, the oxygen transmission rate is 0.70cc / m at a temperature of 23°C and a relative humidity of 60%. 2 ·day·atm or less, and after the boil test and the Gelbo Flex test, the oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 0.70cc / m 2 ·day·atm or less, and after the boiling test, the oxygen transmission rate is 0.50cc / m at a temperature of 23°C and a relative humidity of 60%. 2·day·atm or less, and after the boil test and the Gelbo Flex test, the oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 0.50cc / m 2 It is particularly preferable that the temperature is 100°C or less. The boil test, the Gelbo flex test, and the measurement of oxygen transmission rate at a temperature of 23° C. and a relative humidity of 60% can be specifically carried out by the methods described in the examples below.
[0087] In addition, the laminate film of the present invention has a peel strength of 3.0 N / 15 mm or more after a boil test in a T-peel test according to JIS K6854-3, because the gas barrier property of the laminate film is not easily deteriorated even after a wet heat treatment and a Gelbo flex test. After the boiling test, the peel strength measured by applying water to the peeled surface is preferably 3.0 N / 15 mm or more in a T-peel test in accordance with JIS K6854-3. It is more preferable that the peel strength of the laminate film of the present invention after the boil test is 3.1 N / 15 mm or more in the T-peel test, and that the peel strength measured after the boil test with water attached to the peel surface is 3.1 N / 15 mm or more in the T-peel test, and it is even more preferable that the peel strength after the boil test is 3.2 N / 15 mm or more in the T-peel test, and that the peel strength measured after the boil test with water attached to the peel surface is 3.2 N / 15 mm or more in the T-peel test. The peel strength after the boil test and the peel strength measured by applying water to the peeled surface after the boil test can be measured specifically by the method described in the examples below.
[0088] <Laminate film manufacturing method> The laminate film of the present invention can be produced by forming other layers, if necessary, on the gas barrier film of the present invention, and laminating a heat seal layer, if necessary via an adhesive layer.
[0089] [Second lamination film] The second laminate film of the present invention comprises a gas barrier film having a substrate, a layer (A') containing a cured product of an epoxy resin, and a layer (B') adjacent to the layer (A') containing a polycarboxylic acid polymer and a polyvalent metal salt of the polycarboxylic acid polymer, the layer (B') having a thickness of 120 nm or more and 240 nm or less, and a sealant layer; After the boiling test, the oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 1.00cc / m 2 ·day·atm or less, and After the boil test, the Gelbo Flex test was performed under conditions of 23°C and 50% relative humidity according to ASTM F392. The oxygen permeability at 23°C and 60% relative humidity was 1.00cc / m 2 ·day·atm or less, The peel strength after the boiling test is 3.0N / 15mm or more in a T-peel test conforming to JIS K6854-3, and After the boil test, the peel strength measured by applying water to the peeled surface is 3.0N / 15mm or more in a T-peel test in accordance with JIS K6854-3.
[0090] The second laminate film of the present invention has a similar effect to the first laminate film, and as specified above, has high gas barrier properties even after moist heat treatment and further after the Gelbo flex test after moist heat treatment.
[0091] The boil test, Gelbo flex test, and the oxygen permeability at a temperature of 23°C and a relative humidity of 60%, the peel strength after the boil test, and the peel strength measured by applying water to the peeled surface after the boil test can be measured specifically by the methods described in the examples below.
[0092] The second laminate film of the present invention has an oxygen transmission rate of 0.95 cc / m at a temperature of 23° C. and a relative humidity of 60% after a boiling test. 2·day·atm or less, and after the boil test and the Gelbo Flex test, the oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 0.95cc / m 2 ·day·atm or less, and after the boiling test, the oxygen transmission rate is 0.90cc / m at a temperature of 23°C and a relative humidity of 60%. 2 ·day·atm or less, and after the boil test and the Gelbo Flex test, the oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 0.90cc / m 2 ·day·atm or less, and after the boiling test, the oxygen transmission rate is 0.70cc / m at a temperature of 23°C and a relative humidity of 60%. 2 ·day·atm or less, and after the boil test and the Gelbo Flex test, the oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 0.70cc / m 2 It is even more preferable that the temperature is 100°C or less. Moreover, it is more preferable that the peel strength of the second laminate film of the present invention after the boiling test is 3.1 N / 15 mm or more in the T-peel test, and the peel strength measured by attaching water to the peel surface after the boiling test is 3.1 N / 15 mm or more in the T-peel test. It is more preferable that the peel strength after the boiling test is It is even more preferable that the peel strength is 3.2 N / 15 mm or more, and that the peel strength measured by applying water to the peeled surface after the boiling test is 3.2 N / 15 mm or more in the T-peel test.
[0093] In the second laminate film of the present invention, the substrate may be the same as that described above. In the second laminate film of the present invention, the layer (A') contains a cured product of an epoxy resin, that is, the layer (A') contains a reaction product of an epoxy resin having an epoxy group and an epoxy resin curing agent. The epoxy resin used in layer (A') preferably has two or more epoxy groups in one molecule, more preferably has three or more epoxy groups in one molecule, and even more preferably has four or more epoxy groups in one molecule. Examples of epoxy resins include epoxy resins having a glycidyl amine moiety or a glycidyl ether moiety derived from a compound having an amino group or a hydroxyl group, which is a saturated or unsaturated aliphatic compound, alicyclic compound, aromatic compound, heterocyclic compound, or a combination thereof; and compounds having an alicyclic epoxy group moiety derived from a compound having a carboxy group, which is a saturated or unsaturated aliphatic compound, alicyclic compound, aromatic compound, heterocyclic compound, or a combination thereof. The epoxy resin can be appropriately selected from conventionally known epoxy resins, but it is preferable to use the same ones as those explained in connection with layer (A). The epoxy resin curing agent and other components used as necessary may be the same as those explained in the layer (A).
[0094] The layer (B') is located adjacent to the layer (A') and contains a polycarboxylic acid polymer and a polyvalent metal salt of the polycarboxylic acid polymer. In the layer (B'), the polycarboxylic acid polymer may be the same as that in the layer (B). Examples of polyvalent metal ions constituting the polyvalent metal salt include divalent or higher metal ions such as magnesium ions, calcium ions, barium ions, zinc ions, copper ions, cobalt ions, nickel ions, aluminum ions, and iron ions. Among these, it is preferable to use at least one metal ion selected from the group consisting of magnesium ions, calcium ions, barium ions, zinc ions, and aluminum ions.
[0095] The gas barrier film used in the second laminate film of the present invention can be produced in the same manner as the gas barrier film of the present invention. The polyvalent metal salt of the polycarboxylic acid polymer is preferably produced in the same manner as the magnesium salt of the polycarboxylic acid polymer.
[0096] In the second laminate film of the present invention, the sealant layer and other layers may be the same as those described in the first laminate film, and it can be produced in the same manner as the first laminate film.
[0097] III. Packaging The package of the present invention is a package including the laminate film of the present invention. Since the package of the present invention includes the laminate film of the present invention, the package of the present invention has high gas barrier properties and is resistant to deterioration of the gas barrier properties even after moist heat treatment and Gelbo flex test. Examples of the packaging body include flat pouches, standing pouches, pouches with nozzles, pillow bags, gusset bags, bullet-shaped packaging bags, packaging containers, etc., and by arbitrarily selecting the material composition of the laminate film, it is possible to impart easy opening, easy tearing, shrinkability, microwave compatibility, ultraviolet blocking properties, design properties, etc. Specific shapes of other packaging bodies include bottles, trays, cups, tubes, and the lids and mouth sealants of these containers. For example, a packaging bag can be produced by folding the laminate film of the present invention in half, overlapping the sealant layer surfaces so that they face each other, heat sealing the ends to form a cylindrical package, sealing the bottom, filling the contents, and then sealing the top.
[0098] The laminate film of the present invention can be folded or overlapped to face the inner layer surface, and the peripheral edge can be heat sealed by, for example, a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type (pillow seal type), a pleated seal type, a flat bottom seal type, a square bottom seal type, a gusset seal type, etc. In addition, for example, a self-supporting packaging bag (standing pouch) can also be produced.
[0099] In the above, the heat sealing can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, etc.
[0100] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. EXAMPLES
[0101] The following Examples 1 to 13 correspond to the first laminate film and the second laminate film, and Example A corresponds to the second laminate film. [Evaluation method] <Layer thickness measurement> The thickness of each layer was measured by preparing ultrathin slices of the obtained laminate film and observing the cross section with a transmission electron microscope (TEM).
[0102] <Oxygen permeability measurement> Using an oxygen permeability measuring device (manufactured by Modern Control (mocon) [model name: OX-TRAN 2 / 21]), set the oxygen supply side to be the base layer side of the gas barrier film, and measure the oxygen permeability (cc / m2) in accordance with JIS K7126 under measurement conditions of a temperature of 23°C and a relative humidity of 60%. 2 ·day·atm) was measured.
[0103] <Boiling test> The obtained laminate film was cut into two pieces of A4 size, the two pieces were stacked with the sealant layer facing each other, and the ends and bottom were heat-sealed to form a packaging bag. The sample in which 150 mL of pure water was sealed inside the packaging bag was placed in a high-temperature, high-pressure cooking sterilizer capable of performing boiling and cooling under the following conditions, and boiled for 30 minutes in hot water at 95°C, then replaced with water at 23°C and cooled for 15 minutes. The water was then replaced with water at 23°C again and cooled for 10 minutes to complete the boiling process.
[0104] <Gelboflex test> A Gelbo Flex test was carried out in accordance with ASTM F392 using a Gelbo Flex Tester (manufactured by Tester Sangyo Co., Ltd.). After the boiling test, the packaging bag was cut to A4 size and set into a cylindrical shape with a diameter of 90 mm with the substrate side facing inwards. The bag was then twisted 440° at 40 times per minute, pushed in 90 mm, and then moved straight forward 65 mm, 50 times, under conditions of 23°C temperature and 50% relative humidity.
[0105] <Peel strength> (Normal peel strength after boiling test: dry) After a boiling test at 95°C for 30 minutes, the water was removed from the packaging bag and a sample was cut into a 15 mm wide strip. For this sample, the peel strength between the substrate of the laminate film and the layer formed on the substrate was measured in accordance with JIS K6854-3 using a tensile tester (manufactured by Orientec Co., Ltd. [model name: Tensilon universal material testing machine]). For the measurement, first, a rectangular test piece 30 was prepared in which the base layer 11 and the layers (12, 13, 14) formed on the base were peeled off by 15 mm in the long side direction, as shown in Fig. 3. Then, as shown in Fig. 4, the base 11 and the already peeled portions of the layers (12, 13, 14) formed on the base were held by grips 31 and 32 of a measuring device, respectively. The grippers 31 and 32 were pulled in opposite directions (180° peeling: T-peel method) perpendicular to the surface direction of the portion where the substrate 11 and the layers (12, 13, 14) formed on the substrate are still laminated, at a speed of 50 mm / min, and the average value of the tensile stress in the stable region (see FIG. 5) was measured. The distance S between the grippers 31 and 32 when pulling started was 30 mm, and the distance S between the grippers 31 and 32 when pulling ended was 60 mm. FIG. 5 is a diagram showing the change in tensile stress with respect to the distance S between the grippers 31 and 32. As shown in Figure 5, the change in tensile stress with respect to the distance S passes through a first region and enters a second region (stable region) where the rate of change is smaller than that of region 1. The average value of the tensile stress in the stable region was measured, and this value was taken as the peel strength between the substrate of the laminate film and the layer formed on the substrate. (Wet peel strength after boil test) The water-wet peel strength was measured in the same manner as in measuring the normal peel strength, except for the following points. In measuring the water-exposed peel strength, the substrate of the test piece and the layer formed on the substrate were peeled off by 15 mm, and the peel strength was measured when water was present at the adhesive interface between the substrate and the layer formed on the substrate. In measuring the water-attached peel strength, the peel strength was measured in such a state that 100 μL of water was dropped with a dropper onto the boundary between the part where the substrate and the layer formed on the substrate remained bonded and the part where the substrate and the layer formed on the substrate had been peeled away, when viewed along the longitudinal direction of the test piece 30.
[0106] <Visual evaluation after boil test> After the boiling test, the packaging bag was opened, the contents were discarded, and the heat-sealed end of the laminate film was cut off to recover the laminate film. Both sides of the recovered laminate film were wiped with a dry cloth to remove moisture, and then the laminate film was visually observed. (Evaluation Criteria) ○: Transparent and no gaps occurred between the film layers ×: Whitening or gaps between film layers occurred
[0107] Example 1 (1) Manufacturing of gas barrier films (1-1) Formation of layer (A) 46.1 g of methanol was weighed out, and 5.2 g of ethyl acetate was added thereto to prepare a methanol / ethyl acetate mixed solvent. 2.7 g of an epoxy resin curing agent (polyamine, manufactured by Mitsubishi Gas Chemical Company, trade name Maxive C-93T) was dissolved therein. Furthermore, 1.0 g of an epoxy resin having four or more epoxy groups per molecule (N,N,N',N'-tetraglycidylmetaxylylenediamine, manufactured by Mitsubishi Gas Chemical Company, trade name TETRAD-X) was added and dissolved to prepare a curable composition for forming layer (A). The layer (A)-forming curable composition was applied to a 15 μm-thick nylon film substrate using a wire bar, and the coating was then dried for 2 minutes at 140° C. The dried coating was aged at 55° C. for 24 hours to complete the reaction and cure, thereby obtaining a film (substrate 11 / layer (A) 12) in which layer (A) was formed on the substrate.
[0108] (1-2) Formation of layer (B) 5 g of polyacrylic acid (abbreviated as PAA, Nippon Shokubai, product name AS-58, number average molecular weight 106,000) was dissolved in 95 g of pure water to prepare a polyacrylic acid aqueous solution. 263 g of pure water was added to the prepared polyacrylic acid aqueous solution, and then 2.3 g of magnesium chloride (Fujifilm Wako Pure Chemical Industries, Ltd.) (Mg 2+ (0.7 chemical equivalents relative to the carboxyl groups of polyacrylic acid) was added and dissolved to prepare a composition for forming layer (B). The layer (B)-forming composition was applied directly onto the layer (A) of the film using a wire bar. The amount of coating was appropriately adjusted so that the layer thickness after drying would be as shown in Table 1. The coating was then dried at 80° C. for 1 minute to obtain a gas barrier film 10 (substrate 11 / layer (A) 12 / layer (B) 13) in which layer (A) and layer (B) were formed on the substrate. The column for layer (B) in Table 1 shows the polyvalent metal compound used to form the salt of the polycarboxylic acid polymer.
[0109] (2) Manufacturing of laminated films A two-component curing polyurethane adhesive (not shown) was applied onto layer (B) 13 of the gas barrier film 10 obtained above, and the resulting film was dried and dry laminated with a 70 μm-thick non-axially oriented polypropylene film as a sealant layer 14 to produce a laminate film 20. The evaluation results obtained are shown in Table 1.
[0110] (Examples 2 to 5, Comparative Examples 1 to 3) In Example 1, when producing the gas barrier film, the solid content concentration and coating amount of the composition for forming layer (B) were appropriately adjusted so that the layer thickness after drying of layer (B) would be the thickness shown in Table 1. A gas barrier film and a laminate film were produced in the same manner as in Example 1. The obtained evaluation results are shown in Table 1. In addition, an element distribution analysis was performed by EDX (energy dispersive X-ray analysis) using an ultrathin slice of the laminate film used for the layer thickness measurement. The results of Example 3 are shown in FIG.
[0111] Example 6 In Example 1, when preparing the composition for forming the layer (B) in the production of the gas barrier film, 1.4 g of magnesium hydroxide (manufactured by Konoshima Chemical Co., Ltd.) was used instead of 2.3 g of magnesium chloride. 2+ A gas barrier film and a laminate film were produced in the same manner as in Example 1, except that 7.2 g of hydrochloric acid and 0.7 chemical equivalents based on the carboxyl group of polyacrylic acid were used to dissolve the polyacrylic acid in pure water. The evaluation results are shown in Table 1.
[0112] Example 7 A gas barrier film and a laminate film were produced in the same manner as in Example 1, except that, instead of using 2.3 g of magnesium chloride, 1.4 g of magnesium hydroxide (manufactured by Konoshima Chemical Co., Ltd.) and 6.5 g of nitric acid were dissolved in pure water when preparing the composition for forming layer (B) in producing the gas barrier film. The obtained evaluation results are shown in Table 1.
[0113] Example 8 A gas barrier film and a laminate film were produced in the same manner as in Example 1, except that the coating amount of the curable composition for forming the layer (A) was appropriately adjusted so that the layer thickness after drying and curing of the layer (A) in producing the gas barrier film in Example 1 would be the thickness shown in Table 1. The obtained evaluation results are shown in Table 1.
[0114] (Examples 9 to 13) In Example 1, in the layer (B) forming composition for producing a gas barrier film, the chemical equivalent of magnesium chloride to the carboxyl group of polyacrylic acid was adjusted to be as shown in Table 2, and the solid content concentration was set to 5 mass%, except that a layer (B) forming composition was prepared in the same manner as in Example 1. In addition, a gas barrier film was produced and a laminate film was produced in the same manner as in Example 1, except that the coating amount of the layer (B) forming composition was appropriately adjusted so that the layer thickness after drying of the layer (B) was the thickness shown in Table 2. The obtained evaluation results are shown in Table 2.
[0115] (Second Laminate Film Example A) In Example 11, in the production of the gas barrier film, instead of 1.0 g of an epoxy resin having four or more epoxy groups in one molecule in the curable composition for forming layer (A) (N,N,N',N'-tetraglycidyl metaxylylenediamine, manufactured by Mitsubishi Gas Chemical Company, trade name TETRAD-X), 1.2 g of an epoxy resin having three epoxy groups in one molecule (N-[2-methyl-4-(oxiranylmethoxy)phenyl]-N-(oxiranylmethyl)oxiranemethanamine) manufactured by Sumitomo Chemical Company, trade name Sumiepoxy ELM-100) was used to prepare a curable composition for forming layer (A') and used instead of the curable composition for forming layer (A), a gas barrier film was produced in the same manner as in Example 11, and a laminate film was produced. The obtained evaluation results are shown in Table 2.
[0116] Comparative Example 4 A gas barrier film and a laminate film were produced in the same manner as in Example 1, except that, instead of using 5 g of polyacrylic acid, 5 g of polyvinyl alcohol (abbreviated as PVA, manufactured by Kuraray, product name PVA-124) was used and dissolved in pure water when preparing the composition for forming layer (B) in producing the gas barrier film in Example 1. The obtained evaluation results are shown in Table 1.
[0117] Comparative Example 5 A gas barrier film and a laminate film were produced in the same manner as in Example 1, except that an oxazoline resin solution (manufactured by Nippon Shokubai, product name WS-300) was used instead of the curable composition for forming layer (A) used in producing the gas barrier film in Example 1, and was similarly coated, and then the coating film was dried and cured at 60° C. for 3 minutes. The obtained evaluation results are shown in Table 1.
[0118] Comparative Example 6 A gas barrier film and a laminate film were produced in the same manner as in Example 1, except that magnesium chloride was not used in preparing the composition for forming layer (B) in producing the gas barrier film in Example 1. The obtained evaluation results are shown in Table 1.
[0119] Comparative Example 7 A gas barrier film and a laminate film were produced in the same manner as in Example 1, except that the layer (A) was not formed when producing the gas barrier film in Example 1. The obtained evaluation results are shown in Table 1.
[0120] Comparative Example 8 A gas barrier film and a laminate film were produced in the same manner as in Example 1, except that the layer (B) was not formed when producing the gas barrier film in Example 1. The obtained evaluation results are shown in Table 1.
[0121] Comparative Example 9 A gas barrier film and a laminate film were produced in the same manner as in Example 8, except that the layer (B) was not formed when producing the gas barrier film in Example 8. The obtained evaluation results are shown in Table 1.
[0122] Comparative Example 10 In Example 11, a gas barrier film was produced in the same manner as in Example 11, except that a polyester film (IB-PET-P manufactured by Dai Nippon Printing Co., Ltd.) on which aluminum oxide was vapor-deposited was used instead of a nylon film having a thickness of 15 μm as a substrate, and layer (A) was not formed, but layer (B) was formed using an applicator. The obtained evaluation results are shown in Table 2.
[0123] Comparative Example 11 In Example 11, a gas barrier film was produced in the same manner as in Example 11, except that a polyester film (IB-PET-P manufactured by Dai Nippon Printing Co., Ltd.) on which aluminum oxide was vapor-deposited was used instead of a nylon film having a thickness of 15 μm as a substrate, and layer (A) was formed using an applicator without forming layer (B). The obtained evaluation results are shown in Table 2.
[0124] (Comparative Examples 12 to 14) A gas barrier laminate was obtained in the same manner as in Examples 3 to 5 of Patent Document 1 (WO 2010 / 001836). The layer (A) containing an alkaline compound of a polyvalent metal is white and opaque, but by laminating a layer (B) containing polyacrylic acid on the layer (A), the layer (A) and the layer (A) become transparent. After laminating the layer (B), heat shrinkage occurred during the drying process, causing wrinkles and deteriorating the appearance. It is presumed that in this manufacturing method, a neutralization reaction between carboxylic acid and alkali occurs after the formation of the two layers, and heat shrinkage is likely to occur due to the heat of neutralization. It has been shown that the manufacturing method of Patent Document 1 (WO 2010 / 001836) is prone to unevenness and heat shrinkage, and is prone to deterioration of the appearance in the first place.
[0125] [Table 1]
[0126] [Table 2] In the table, "<0.1" indicates that it was less than 0.1.
[0127] The gas barrier films and laminate films of Examples 1 to 13, which have a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule and a layer (B) adjacent to the layer (A) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer, and in which the thickness of the layer (B) is 120 nm or more and 240 nm or less, have been shown to have high gas barrier properties from the initial stage of production, and are resistant to deterioration in gas barrier properties even after moist heat treatment (boil test) and further after a Gelbo flex test following the moist heat treatment (boil test). In addition, an element distribution analysis was performed by EDX (energy dispersive X-ray analysis) using ultrathin slices of the laminate film. As shown in Figure 6, the anion (Cl - ) is a magnesium ion (Mg 2+It was shown that the amount of ZnO was greater in layer (A) than in layer (B), where ZnO is present, and that the ZnO was not present in the outermost surface of layer (B) (the surface of layer (B) opposite to the surface having layer (A)).
[0128] On the other hand, in Comparative Example 1 in which the layer (B) had a thickness of less than 120 nm, the gas barrier property was shown to deteriorate after the wet heat treatment. This is presumably because when the layer (B) had a thickness that was too small, the gas barrier property due to crosslinking between the polycarboxylic acid and magnesium ions in the layer (B) became insufficient. In Comparative Example 2, in which the layer (B) had a thickness of more than 240 nm, the gas barrier film itself was shown to have poor gas barrier properties. In Comparative Example 3, in which the layer (B) was thicker, the gas barrier film itself was poor in gas barrier properties, and the layer (B) peeled off after moist heat treatment. It was presumed that if the layer (B) was too thick, the adhesion due to the crosslinking reaction between the layer (A) and the layer (B) would be insufficient. In Comparative Example 4, in which polyvinyl alcohol was used instead of polyacrylic acid as the polymer of the layer (B), the gas barrier properties of the gas barrier film itself and the initial gas barrier properties of the laminate film were poor, and the layer (B) peeled off after wet heat treatment. It was presumed that the crosslinking of polyvinyl alcohol with magnesium ions results in poor gas barrier properties, and that when the functional group reactive with the layer (A) is a hydroxyl group contained in the polyvinyl alcohol, the adhesion due to the crosslinking reaction between the layer (A) and the layer (B) becomes insufficient. In Comparative Example 5, in which a cured product of an oxazoline resin was used instead of the cured product of an epoxy resin in the layer (A), the gas barrier property of the gas barrier film itself was shown to be inferior. In Comparative Example 6, where no magnesium salt was formed in the layer (B), the gas barrier properties of the gas barrier film alone and the initial gas barrier properties of the laminate film were poor, and the layer (B) peeled off after wet heat treatment. It is presumed that the polyacrylic acid having unreacted carboxyl groups that remained without reacting with magnesium was dissolved in hot water during boiling, causing the layer (B) to peel off. In Comparative Example 7, in which the layer (A) was not formed, the gas barrier properties of the gas barrier film alone and the initial gas barrier properties of the laminate film were poor, and furthermore, a problem occurred in which the layer (B) peeled off after wet heat treatment. In Comparative Examples 8 and 9 where the layer (B) was not formed, the gas barrier properties of the gas barrier film alone and the laminate film were poor, even in Comparative Example 9 where the layer (A) was thickened, and the peel strength could not be measured because a test piece 30 could not be prepared. This is presumably because the adhesion between the layer (A) and the substrate was too strong. In Comparative Example 10, in which a polyester film vapor-deposited with aluminum oxide was used instead of a 15 μm-thick nylon film as the base material when producing a gas barrier film, and the layer (A) was not formed, the gas barrier properties of the gas barrier film alone were improved compared to Comparative Example 7 thanks to the vapor-deposited aluminum oxide film, but the gas barrier properties of the laminate film were inferior initially, after moist heat treatment, and after the Gelbo Flex test after moist heat treatment. In Comparative Example 11, in which a polyester film vapor-deposited with aluminum oxide was used instead of a 15 μm-thick nylon film as the base material when producing a gas barrier film, and layer (B) was not formed, the gas barrier properties of the gas barrier film alone and the initial gas barrier properties of the laminate film and after moist heat treatment were improved compared to Comparative Example 8 thanks to the aluminum oxide vapor-deposited film, but it was shown that the gas barrier properties deteriorated after the Gelbo flex test after moist heat treatment due to the influence of the aluminum oxide vapor-deposited film. [Explanation of symbols]
[0129] 10 Gas barrier film 11 Base material 12 layers (A) 13 layers (B) 14 Sealant layer 20 Laminating film 30 Test Pieces 31, 32 Grip
Claims
1. A substrate; a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule; a layer (B) adjacent to the layer (A) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer; A gas barrier film, wherein the layer (B) has a layer thickness of 120 nm or more and 240 nm or less.
2. Oxygen permeability at a temperature of 23°C and a relative humidity of 60% is 1.00 cc / m 2 The gas barrier film according to claim 1, wherein the gas barrier film has a viscosity of 0.5 -day-atm or less.
3. The present invention relates to a coating composition comprising a substrate, a layer (A) containing a cured product of an epoxy resin having four or more epoxy groups in one molecule, and a layer (B) adjacent to the layer (A) containing a polycarboxylic acid polymer and a magnesium salt of the polycarboxylic acid polymer, the layer (B) having a thickness of A gas barrier film having a thickness of 120 nm or more and 240 nm or less; A laminate film having a sealant layer.
4. After the boil test, the oxygen transmission rate at a temperature of 23°C and a relative humidity of 60% is 1.00 cc / m 2 ・day・atm or less, and After the boil test, a Gelbo Flex test was performed under conditions of a temperature of 23° C. and a relative humidity of 50% in accordance with ASTM F392. The oxygen transmission rate at a temperature of 23° C. and a relative humidity of 60% was 1.00 cc / m 2 The laminate film according to claim 3, wherein the viscosity is 0.05-0.5 MPa or less.
5. The peel strength after the boiling test is 3.0 N / 15 mm or more in a T-peel test in accordance with JIS K6854-3, and 5. The laminate film according to claim 3, wherein the peel strength measured by applying water to the peel surface after the boiling test is 3.0 N / 15 mm or more in a T-peel test in accordance with JIS K6854-3.
6. A packaging body comprising the laminate film according to any one of claims 3 to 5.
Citation Information
Patent Citations
Multi-layer packaging material for oxygen-sensitive foods and beverages
JP2001506550A
Gas barrier polyolefin laminated film
JP2004025616A
Manufacturing method of gas-barrier laminate
JP2004315585A
Gas barrier coating and gas barrier laminate prepared by using the same
JP2005272757A
Multilayer film
WO2005037535A2